PENERAPAN LAYANAN KONSELING BEHAVIORISTIK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENGATASI PERILAKU MEMBOLOS SISWA VIII SMP TERPADU AKN MARZUQI - Vibrianti, Sari Rafna; Kiswantoro, Arista; Mahardika, Nur (Universitas Muria Kudus, 2023)
The aims of this research are: 1) To find out the factors that cause students to experience frequent truancy. 2) To overcome student truancy behavior by applying behavioristic counseling with self-management techniques to AKN Marzuqi Integrated Junior High School students. Ditching behavior is an act that is not approved by the school, usually without the knowledge of parents. The act of skipping school is something that is put forward as an answer to the boredom that students often experience with teaching and learning activities at school. In the end, truancy becomes a phenomenon that hinders the learning process of students. Skipping is something that is intentional by students that often occurs in junior high school (SMP) or high school (SMA) students.